2010
DOI: 10.1177/0898010110373656
|View full text |Cite
|
Sign up to set email alerts
|

Forging Partnerships Between Rural Women With Chronic Conditions and Their Health Care Providers

Abstract: Successful adaptation to chronic illness is enhanced by active client-health care provider partnerships. The purposes of this article are to (a) examine the health care partnership needs of western rural women with chronic illness who participated in a computer-based support and education project, (b) describe how the role of the women in the partnership can be maximized by the use of a personal health record and improving health literacy, and (c) discuss ways health care providers can enhance their role in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Nurses can use a wide range of effective communication strategies and interpersonal skills to appropriately establish and maintain a nurse‐patient relationship . However, the health care climate, with its reduced appointment times and emphasis on economics, has made it difficult for health care providers to establish relationships with patients and provide the health care support needed.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nurses can use a wide range of effective communication strategies and interpersonal skills to appropriately establish and maintain a nurse‐patient relationship . However, the health care climate, with its reduced appointment times and emphasis on economics, has made it difficult for health care providers to establish relationships with patients and provide the health care support needed.…”
Section: Discussionmentioning
confidence: 99%
“…Patients' cultural, religious/spiritual, social, language, and decision‐making needs should be addressed as part of the process and may involve family members as applicable . Nurses are well‐positioned to establish health care relationships with patients, as nursing has been ranked the most trusted profession for 15 years in a row …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…7,28-30 31 In remote areas, technology such as internet support groups, telehealth communication, and teaching models on disease states have been effective tools for improving health literacy, medication adherence, patient engagement and patient empowerment, especially for women. 7,12,23 Our study showed use of internet by respondents for preventative care and some future interest in using telehealth solutions for healthcare. For many rural areas, telehealth has been a great bridging opportunity to improve access and patient care.…”
Section: Discussionmentioning
confidence: 99%
“…22 Details about patient-centric issues were gleaned from the participants using a focus group protocol based on the existing literature, to guide the focus group discussions. 4,7,18,23 The focus group sessions were held in a neutral location -either at the University or the hospital conference room. Demographic information was also collected from each participant.…”
Section: Methodsmentioning
confidence: 99%